Neck Management in cT1N0 Tongue Squamous Cell Carcinoma as Determined by Sonographic Depth of Invasion - Wu, Yao; Zhang, Xu; Dai, Liyuan; Fang, Qigen; Du, Wei (Frontiers in Oncology, 2022)
Objectives: To compare the oncologic outcomes in patients with cT1N0 tongue squamous cell carcinoma (SCC) who underwent different neck management strategies stratified by sonographic depth of invasion (DOI). Methods: The included patients were retrospectively enrolled, and divided into two groups: observation (OBS) and elective neck dissection (END). The regional control (RC) and disease-specific survival (DSS) rates were compared and stratified by sonographic DOI. Results: The mean sonographic and pathologic DOIs were 3.8 mm and 3.7 mm, respectively; the two DOIs were significantly correlated (Spearman correlation coefficient 0.974. p<0.001). In patients with sonographic DOI<4.0 mm, the 5-year RC rates were 73% and 89% in the OBS and END groups, respectively, and were not significantly different. However, in patients with sonographic DOI≥4.0 mm, the 5-year RC rate was significantly different between the OBS (57%) and END (80%) groups (p=0.031). In patients with sonographic DOI<4.0 mm, the 5-year DSS rates were 79% and 89% in OBS and END groups, respectively, and were not significantly different. However, in patients with sonographic DOI≥4.0 mm, the 5-year DSS rate was significantly different between the OBS (67%) and END (86%) groups (p=0.033). Conclusions: Sonographic DOI was notably correlated with pathologic DOI. Moreover, there was a significant survival difference between the OBS and END groups in cT1N0 tongue SCC patients with sonographic DOI≥4.0 mm but not in those with sonographic DOI<4.0 mm. Our study provides a useful method to aid decision-making in the clinical setting for this patient group.